Guidelines for Healthy Housing Development for All - Jarutach, Trirat (Journal of Architectural/Planning Research and Studies (JARS), 2022)
Good health and well-being are some of the most significant trends in the contemporary world. Because of the coronavirus (COVID-19) pandemic, Thai people have healthier lifestyles, more concerned about their health, and consequently, change their behaviours to adapt to the ‘new normal’ ways of living. According to the result of an opinion survey by Suan Dusit Poll, 45.39% have changed their attention to healthcare by exercising, eating more healthy products, and emphasising housing and health education, and criteria for evaluating residential buildings have been established. The research study shows that the assessment criteria such as LEED and BREEAM mainly focus on energy and resource efficiency to reduce environmental impacts. At the same time, WELL and CASBEE tools are primarily occupant-oriented and include universal design principles. All of these aim for improving residents’ quality of life. The analysis of factors for healthy housing development indicates that residents were satisfied with eight essential factors such as location, lighting, materials, water quality, comfort, sound, air quality and energy conservation. Among these aspects, comfort and sound are the most critical factors. The results highlight the emphasis of project developers and architects. In the context of Thailand, the SOOK Building Standard by Thai Green Building Institute (TGBI) is a criterion used to evaluate both residential and other types of buildings. The objective of this research is to produce building evaluation criteria for residential and other building types. Consequently, future studies are recommended to study the physical characteristics and satisfaction of residents within a project with a healthy home concept., particularly in the projects that have received a certificate of building assessment criteria.